The pallidotomy debate. - Carroll, C; Scott, R; Davies, L; Aziz, T (1998)
It has been suggested that image-guidance and macro-stimulation alone are not sufficiently accurate to result in safe and effective lesion localization in pallidotomy for Parkinson's disease when compared with micro-electrode recording. This review analyses the data in the series published to date, and compares the safety and efficacy of the two techniques, finding no evidence to support this claim. In addition, evidence regarding the necessary accuracy of lesion placement is reviewed.